Discovery of the first small-molecule CsrA–RNA interaction inhibitors using biophysical screening technologies. (June 2016) - Maurer, Christine K; Fruth, Martina; Empting, Martin; Avrutina, Olga; Hoßmann, Jörn; Nadmid, Suvd; Gorges, Jan; Herrmann, Jennifer; Kazmaier, Uli; Dersch, Petra; Müller, Rolf; Hartmann, Rolf W
Aim: CsrA is a global post-transcriptional regulator protein affecting mRNA translation and/or stability. Widespread among bacteria, it is essential for their full virulence and thus represents a promising anti-infective drug target. Therefore, we aimed at the discovery of CsrA–RNA interaction inhibitors.Results & methodology: We followed two strategies: a screening of small molecules (A) and an RNA ligand-based approach (B). Using surface plasmon resonance-based binding and fluorescence polarization-based competition assays, (A) yielded seven small-molecule inhibitors, among them MM14 (IC50 of 4 µM). (B) resulted in RNA-based inhibitor GGARNA (IC50 of 113 µM).Conclusion: The first small-molecule inhibitors of the CsrA–RNA interaction were discovered exhibiting micromolar affinities. These hits represent tools to investigate the effects of CsrA–RNA interaction inhibition on bacterial virulence.